The effects of a 6-week controlled, hypocaloric ketogenic diet, with and without exogenous ketone salts, on cognitive performance and mood states in overweight and obese adults - Kackley, Madison L.; Brownlow, Milene L.; Buga, Alex; Crabtree, Chris D.; Sapper, Teryn N.; O’Connor, Annalouise; Volek, Jeff S. (Frontiers in Neuroscience, 2022)
Background Ketogenic diets are a commonly used weight loss method, but little is known how variations in sodium content and ketones influence cognition and mood during the early keto-adaptation period. Objectives To investigate the effects of an exogenous ketone salt (KS) as part of a hypocaloric KD on mood and cognitive outcomes in overweight and obese adults. A secondary objective was to evaluate changes in biochemical markers associated with inflammatory and cognitive responses. Materials and methods Adults who were overweight or obese participated in a 6-week controlled-feeding intervention comparing hypocaloric diets (∼75% of energy expenditure). KD groups received twice daily ketone salt (KD + KS; n = 12) or a flavor-matched placebo, free of minerals (KD + PL; n = 13). A separate group of age and BMI matched adults were later assigned to an isoenergetic low-fat diet (LFD; n = 12) as comparison to KD. Mood was assessed by shortened Profile of Mood States and Visual Analog Mood Scale surveys. Cognitive function was determined by the Automated Neuropsychological Assessment Metrics mental test battery. Results Both KD groups achieved nutritional ketosis. Fasting serum glucose decreased in both KD groups, whereas glucose was unaffected in the LFD. Insulin decreased at week 2 and remained lower in all groups. At week 2, depression scores in the KD + PL group were higher compared to KD + KS. Performance in the math processing and go/no-go cognitive tests were lower for KD + PL and LFD participants, respectively, compared to KD + KS. Serum leptin levels decreased for all groups throughout the study but were higher for KD + KS group at week 6. Serum TNF-α steadily increased for LFD participants, reaching significance at week 6. Conclusion During a short-term hypocaloric diet, no indication of a consistent decline in mood or cognitive function were seen in participants following either KD, despite KD + PL being relatively low in sodium. WK2 scores of “anger” and “depression” were higher in the LFD and KD + PL groups, suggesting that KS may attenuate negative mood parameters during the early intervention stages.